2011
DOI: 10.1071/wf09070
|View full text |Cite
|
Sign up to set email alerts
|

Career stages in wildland firefighting: implications for voice in risky situations

Abstract: Avoidance of injury and death on the fireline may depend on firefighters voicing their concerns, but often this does not occur. Reasons for employee reticence identified in the literature include a perception of various personal costs or a belief that raising concerns is futile. Additionally, the social context may play a significant role. In a qualitative study using in‐depth interviews with 36 wildland firefighters in the US, we explored reasons firefighters do or do not voice concerns. Findings revealed two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Instead, feedback from fire personnel reported that rarely if ever do they turn down an assignment; instead, they commonly negotiate tactics and strategies. Lewis et al (2011) also found the same view on reputation and the same negotiating tactics of experienced wildland fire leaders. These negotiating tactics often do not occur in front of subordinates, and hence are not artifacts, or rather 'readily seen' (Schein 2016) parts of the culture.…”
Section: The Items Fromsupporting
confidence: 57%
See 3 more Smart Citations
“…Instead, feedback from fire personnel reported that rarely if ever do they turn down an assignment; instead, they commonly negotiate tactics and strategies. Lewis et al (2011) also found the same view on reputation and the same negotiating tactics of experienced wildland fire leaders. These negotiating tactics often do not occur in front of subordinates, and hence are not artifacts, or rather 'readily seen' (Schein 2016) parts of the culture.…”
Section: The Items Fromsupporting
confidence: 57%
“…The first factor -Fire Culture Competence -highlights items that emphasise operational competence and critical thinking. The wildland fire culture places high value on these qualities and they are readily identified as competence, confidence, and credibility or reputation (Desmond 2007;Lewis et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrate an intriguing model on how leadership appears to work in wildland firefighting as well as important directions on how to develop such leadership. In wildland firefighting, competence is consistently stressed in various documents including ones listed previously, and in other works such as Desmond's (2007) ethnographic study of wildland firefighting or in the study of Lewis et al (2011) on employee voice as a most prized possession. This was clearly seen in the present study as competence was the central hypothetical cause of how personally genuine supervisors were regarded by crewmembers and of how their integrity was regarded.…”
Section: Advancing Wildland Firefighting Leadership In the Current Inmentioning
confidence: 97%